Концепция периодических переключений типа раннего онтогенеза у Gastropoda (на примере миоценовых Lottiidae Паратетиса) - Анистратенко, О.Ю.; Анистратенко, В.В. (Видавничий дім "Академперіодика" НАН України, 2008)
Based on a detailed study of the morphology of Miocene lottiids, the concept of periodic switching (alterations) in the early ontogeny type of gastropod molluscs is offered. The phenomenon of switching reveals in the loss of pelagic larva and the transition to non-pelagic development; it is known within several modern and fossil groups of Gastropoda. According to the concept suggested, this drastic change in the early development of molluscs not only coincides in time with decrease in the salinity of basins where they inhabited, but is ecologically triggered by this change of the environment. In the cyclic freshening of the corresponding basins, the overcoming of a biologically important barrier of salinity (presumably about 13–15% ) results in the iterative change of the reproductive strategy of molluscs.